TINGKAT KESIBUKAN CHIEF EXECUTIVE OFFICER (CEO) DALAM MENINGKATKAN NILAI PERUSAHAAN: EFEK MODERASI KUALITAS AUDIT - Bramastyasa Gilang Pradata; Riskin Hidayat (MANAJEMEN DEWANTARA, 2025)
This study aims to examine how the level of Chief Executive Officer (CEO) busyness influences the creation of corporate value mediated by Audit Quality. This study was conducted to examine the influence of the Chief Executive Officer's (CEO) busyness on corporate value creation, mediated by audit quality. The level of Chief Executive Officer (CEO) busyness can impact firm value, and audit quality can act as a moderating variable in this relationship. An overly busy CEO may be unable to focus on strategic tasks critical to enhancing firm value. At the same time, a quality audit can ensure accountability and transparency, ultimately increasing investor confidence and firm value. This research was conducted to examine how the level of Chief Executive Officer (CEO) busyness influences the creation of corporate value moderated by Audit Quality. This study was conducted to examine the influence of the Chief Executive Officer's (CEO) busyness on corporate value creation, moderated by audit quality. This study used secondary data obtained from the Indonesia Stock Exchange (IDX) for the observation period of 2022-2024. The sample used included companies in the energy sector in Indonesia. The model analysis used to test the research was Partial Least Squares (PLS). The results of this study showed that CEO busyness has a negative and significant effect on corporate firm value. Furthermore, audit quality exerts a positive and significant influence on corporate firm value. Moreover, the findings reveal that audit quality moderates the relationship between CEO busyness and firm value. Specifically, high quality audits can reduce the negative impact of CEO busyness, reinforcing the importance of external monitoring mechanisms in corporate governance.